PTH-112 Changing trends in hepatocellular carcinoma presentation: a 5-year regional hepatobiliary centre experience in liverpool, uk. (22nd June 2015) - Ladep, NG; Noorullah, O; Sieberhagen, C; Boland, E; Ding, WY; Cross, T; Sturgess, R; Stern, N
Abstract : Introduction: Incidence and mortality of hepatocellular carcinoma (HCC) has been increasing in several Western countries, including England and Wales. We aimed at exploring the yearly trends, stage at presentation, treatment and survival of patients diagnosed with HCC within the North West region of England and Wales. Method: Consecutive patients discussed during 2009 to 2014 in the HCC multidisciplinary team activities of North West region of England and Wales, were included in the study. Trends in age category, mode of diagnosis, BCLC stage at diagnosis and treatment of cases were calculated. Using Kaplan Meier survival statistic, we estimated the overall survival (OS) of HCC cases. Additionally, BCLC stage and age categories were log-ranked to determine trends in survival. Furthermore, independent factors contributing to the survival of these patients were examined using Cox proportional regression modelling. A post hoc analysis of impact of radiofrequency ablation (RFA) versus resection and transplantation (Surgical treatment) on survival was carried out. Results: A total of 671 [512 (76.3%) men; 159 (23.7%) women] persons, mean age –68 yrs (range: 40–98) were diagnosed. There were 36 cases in 2009, rising steadily to 165 in 2014 with significant trend in the proportion of patients diagnosed with BCLC stage 0 disease (p = 0.02). Alcohol, non-alcoholic steatohepatitis (NASH) and viral hepatitis were associated aetiological factors in 156 (23.2%), 103(15.4%) and 99 (14.8%) patients, respectively. 387 (77.1%) had HCC in the background of cirrhosis, and majority; 182 (27.8%) were at BCLC stage B clinical stage at diagnosis. Median overall survival (OS) was 14 months (range, 11–16); and 1, 2 and 4 yr survival rates of 50.4%, 30.9% and 13.1%, respectively. Independent predictors of mortality were AFP≥400 ng/mL (HR: 3.2, p < 0.0001), BCLC D (HR: 2.0, p = 0.02), age below 55 yrs (HR: –0.5, p = 0.03), absence of cirrhosis (HR: –0.5, p = 0.03), curative therapy (HR: –0.2, p < 0.0001) and loco-regional therapy (HR-0.2, p < 0.0001). No significant difference was found in OS of patients treated by Surgical treatment versus RFA (48 months vs 36 months, p = 0.95). Conclusion: Although an increasing rate of early stage diagnosis of HCC is being achieved, this has yet to result in significant survival benefit, suggesting a lead time bias phenomenon. A comparable survival benefit of RFA vs surgical treatment supports the fact that RFA could be an alternative therapy to surgical intervention. Disclosure of interest: None Declared.